African Swine Fever and Hog Cholera Attacks: Perception and Local Knowledge of Farmers in Manokwari - Mulyadi, Mulyadi; Iyai, Deny Anjelus; Widayati, Trisiwi Wahyu; Syufi, Yafed; Sagrim, Meky; Woran, Djonly; Wajo, Muhamad Jen; Salosa, Yeni; Lestaluhu, Aditya (Universitas Bengkulu, 2024)
African Swine Fever (ASF) and Hog Cholera are highly contagious viral diseases in pigs, resulting in losses for pig farmers in Manokwari regency. Farmers cannot avoid panic and resignation. The study aimed to measure pig farmers' attitudes and knowledge about these infectious diseases. Farmers were selected from 12 villages and originated from 8 big ethnics from Papuan and non-Papuan. The findings show that most breeders are still in the early stages of their farming careers and have a long experience. Farmers tend to show concern about African Swine Fever and Hog Cholera. However, their attitudes towards pig diseases are considered less than optimal. Most farmers have fairly good knowledge about African Swine Fever and Hog Cholera. The primary source of information for farmers is obtained from other communities, indicating an exchange of information between pig farmers and the community.